Kebijakan Penggunaan Pemetaan Sosial untuk Mengubah Kawasan Permukiman Kumuh Menjadi Kawasan Wisata di Indonesia Timur - Rulinawaty Rulinawaty; Abdul Rahman; Andi Wijaya; Rahmat Hidayat; Joko Tri Brata (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the effectiveness of the social mapping approach in poverty alleviation and slum management through a strategy of transforming areas into tourist zones. The method used in this study is meta-analysis, which allows the integration of results from various previous studies to evaluate factors that contribute to the success and challenges in slum management. Data were collected through a systematic search in various academic databases, scientific journals, and research reports, with inclusion criteria that include topic relevance, methodological clarity, and data quality. The results show that social mapping plays an important role in creating a more effective intervention model to alleviate poverty and improve the quality of settlements. Collaboration across institutions, both between governments, NGOs, and local communities, is a major factor in ensuring the success of the intervention program. The network of organizations involved shows vertical and horizontal integration that strengthens coordination between sectors and layers of governance, although challenges such as lack of coordination and sectoral egos are still major obstacles. In addition, this study highlights the importance of policy integration and local capacity building through training, education, and knowledge transfer to strengthen institutions and communities. The conclusion is that a comprehensive social mapping approach can effectively address poverty and manage slums sustainably. The transformation of slum areas into tourist destinations not only has an impact on improving physical infrastructure but also encourages economic growth and social welfare of the community. Keywords: Social Mapping, Urban Transformation, Community Engagement, Public Policy, Policy Networks